THEORETICAL AND METHODOLOGICAL FOUNDATIONS FOR MODELING THE FUNCTIONING AND DEVELOPMENT PROCESSES OF REGIONAL POTENTIAL - Bredikhina, Natalia Vladimirovna; Bredikhin , Vladimir; Babyunina, Karina (Journal of Applied Engineering Science, 2022)
The most important economic task of the region’s development is to develop a model of an effective mechanism for the functioning of the regional aggregate potential based on determining the initial state of the organizational and economic system in terms of opportunities for further development. The solution of this complex task in conditions of limited resources puts in the first place the systemic problem of quantitative and qualitative determination of available resources and management of the state of regional potential at a specific time based on the analysis of two phases: use and production. The theoretical and methodological foundations of modelling the processes of functioning and development of regional potential allow us to develop a mathematical multilevel model that ensures optimal management of the region based on the maximum use of labor, production, technical and investment resources. The logical models of functioning and development of economic potential presented in the article are at the same time its formal scheme fixing cause-and-effect relationships in the system.